Kesehatan Mental dan Kesehatan Gigi tidak Mempengaruhi Status Gizi Lanjut Usia di Wilayah Kerja Puskesmas Sukajadi Kota Bandung - Eliza Herijulianti; Kuslan Sunandar (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2013)
Health status of the elderly is influenced by various factors, including elderly endurance. The immune system of the elderly is supported by a good nutritional status. Nutritional status will be better when food intake is adequate, it does not mean quite the availability but more importantly is an intakel ). Elderly who have dental problems will be difficult to sufficient the needs of food intake as well when experiencing mental health problems. Based on the results of health research foundation (Riskesdas) Indonesia in 2007 found an increase in the amount of tooth decay with age ie in the age group 35-44 years of DMF-T average of 4.46 while the age group> 65 years was 18.33. The situation can be caused by poor oral hygiene. Mental health problems in the elderly often occurs because in the later stages of the human life cycle, often tinged with living conditions that are not in line with expectations. Thus the status of mental health and dental health can be affect the elderly nutritional status . The aim of research knowing correlation of the mental and dental health in the elderly with nutrition status in the working area Puskesmas Sukajadi Bandung. Study design is cross-sectional with the elderly population aged 60 years and over. A number of sample are 200 people. Sampling taken at 3 RW with proportional random sampling method. bivariate analysis with Chi Kuardrat test. The results showed there was no significant correlation between mental health and dental health with nutritional status of the elderly.